2013
DOI: 10.1155/2013/519047
|View full text |Cite
|
Sign up to set email alerts
|

Blood Clot Simulation Model by Using the Bond‐Graph Technique

Abstract: The World Health Organization estimates that 17 million people die of cardiovascular disease, particularly heart attacks and strokes, every year. Most strokes are caused by a blood clot that occludes an artery in the cerebral circulation and the process concerning the removal of this obstruction involves catheterisation. The fundamental object of the presented study consists in determining and optimizing the necessary simulation model corresponding with the blood clot zone to be implemented jointly with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In addition to providing computational ef iciency, this elastic coef icient was chosen because it yields an adhesion force on the order of 10 2 pN, assuming a displacement n  on the order of 10 nm. This adhesion force value falls within the range of in vitro estimates that are on the order of 10 0 to 10 4 pN [49][50][51], and the value is within one order of magnitude of that (32 pN) used by another computational model related to thrombectomy [52].…”
Section: Discrete Element Methods Of Platelet Dynamicssupporting
confidence: 65%
“…In addition to providing computational ef iciency, this elastic coef icient was chosen because it yields an adhesion force on the order of 10 2 pN, assuming a displacement n  on the order of 10 nm. This adhesion force value falls within the range of in vitro estimates that are on the order of 10 0 to 10 4 pN [49][50][51], and the value is within one order of magnitude of that (32 pN) used by another computational model related to thrombectomy [52].…”
Section: Discrete Element Methods Of Platelet Dynamicssupporting
confidence: 65%
“…The results of the current study showed that the potential risk factors of keeping dogs (Chi 2  = 3.24, p  = 0.07) and sleeping with dogs (Chi 2  = 3.46, p  = 0.06) showed a tendency toward seropositivity for T. canis but this was not a significant association. Another study of seroprevalence in children in México [14] found that frequent contact with pets was not associated with the presence of toxocariasis (Chi 2  = 0.80, p  = 0.37). A study in Argentina, however, found that contact with animals was an important risk factor for T. canis exposure in children (OR = 5.02, p  = 0.001) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seroprevalence studies in children reported rates of 22.22 % in México [14] compared with 86.75 % in Taiwan in 2014 [15]. To investigate the public health threat caused by toxocariasis in more detail in México, in this study, circulating anti- T. canis antibodies and risk factors for T. canis were investigated in a semirural population in the State of México.…”
Section: Introductionmentioning
confidence: 99%
“…The multiphase model was adapted to model thrombus in an occluded branch of CoW. An alternative strategy, called Bond‐Graph, was suggested by Romero et al . In this model, lumped parameters were implemented to simulate both nonlinear properties of the blood clot and the friction force between clot and walls.…”
mentioning
confidence: 99%
“…In this model, lumped parameters were implemented to simulate both nonlinear properties of the blood clot and the friction force between clot and walls. The Bond‐Graph model was utilized to assess the ratio of clot extraction by “GP” Thrombus Aspiration Device (GPTAD) and self‐expandable stent retriever . The fundamental issue which researchers encounter to simulate aspiration procedure is to represent a reliable constitutive theory for thrombus by considering interactions between thrombus and blood flow.…”
mentioning
confidence: 99%